PENINGKATAN KAPASITAS KELUARGA MELALUI PERAN PENDAMPING PKH DI KABUPATEN MUNA - Fetni; I Rawati; Agus Zul Bay; Maulid (Journal Publicuho, 2025)
This study aims to explore and gain a comprehensive understanding of the role of facilitators in the Family Hope Program (PKH) in improving family capacity. A qualitative approach is employed, with the main focus on obtaining an in-depth understanding of the social dynamics occurring in the field. Techniques included observation, in-depth interviews, focus group discussions (FGDs), and document analysis. Data analysis was conducted using a thematic approach, in which the collected data were grouped into key themes, such as the strategic role of PKH facilitators, their contribution to enhancing family capacity, and the various challenges encountered during the assistance process. The study's results indicated that facilitators play a crucial role in the success of the PKH program, particularly in encouraging improvements in family capacity. In this regard, the role of facilitators encompasses four main functions, as outlined by Jim Ife: facilitators, educators, representatives, and technical implementers. These four roles contribute significantly to changes in KPM behaviour in areas such as education, health, economy, and social awareness. However, the implementation of the facilitator's role has not been fully optimal, especially in technical aspects, due to limited infrastructure, inadequate access to information technology, insufficient administrative support from local policymakers, and program socialisation that has not reached all segments of society. Therefore, the success of PKH assistance is highly dependent on the facilitator's skills and active involvement throughout the process, as well as the need for synergy among various stakeholders to address field challenges.